The zinc-finger protein OEF-1 stabilizes histone modification patterns and promotes efficient splicing in the Caenorhabditis elegans germline. Issue 12 (14th September 2021) - McManus, Catherine E; Mazzetto, Mariateresa; Wei, Guifeng; Han, Mei; Reinke, Valerie
Abstract: To ensure stable transmission of genetic information to the next generation, germ cells frequently silence sex chromosomes, as well as autosomal loci that promote inappropriate differentiation programs. In Caenorhabditis elegans, silenced and active genomic domains are established in germ cells by the histone modification complexes MES-2/3/6 and MES-4, which promote silent and active chromatin states, respectively. These states are generally mutually exclusive and modulation of one state influences the pattern of the other. Here, we identify the zinc-finger protein OEF-1 as a novel modifier of this epigenetic balance in the C. elegans germline. Loss of oef-1 genetically enhances mes mutant phenotypes. Moreover, OEF-1 binding correlates with the active modification H3K36me3 and sustains H3K36me3 levels in the absence of MES-4 activity. OEF-1 also promotes efficient mRNA splicing activity, a process that is influenced by H3K36me3 levels. Finally, OEF-1 limits deposition of the silencing modification H3K27me3 on the X chromosome and at repressed autosomal loci. We propose that OEF-1 might act as an intermediary to mediate the downstream effects of H3K36me3 that promote transcript integrity, and indirectly affect gene silencing as a consequence.